A Living Lab Approach towards Promoting Innovation (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
The transformation projects developed in the context of digital education, sustainable development research and social innovation, and social entrepreneurship have turned the West University of Timişoara (WUT) into an active contributor to the Smart Specialization Strategy at local, regional, and national levels, from its previous status of a passive receiver of policy and R&D strategies. By exploiting open innovation tools integrated into entrepreneurship and aimed at relevant community research, WUT is currently actively involved in the incubation and/or acceleration of more than 200 start-ups, meant to enhance research relevance to actively promote higher technology readiness levels (TRLs) and social acceptance of research results. Building on top of three priority pillars - Digital, Green, and Well-Being, WUT has reconsidered its open innovation strategy and action plan to benefit the community, using a multistakeholder approach. In this context, the Digital & Green Living Lab, with cross-cutting priorities such as entrepreneurship and Culture and Creative Industries, focuses on meaningful transformation projects that contribute to enhanced community well-being. In this direction, important contributions were already achieved toward the digital transformation of educational programs and administrative sectors. Through its sustainable development vision, WUT acts on functional teams working in circular economy consortia, renewable energies, and environmental research.